PERAN SEKOLAH ALAM DALAM MEMPROMOSIKAN KELESTARIAN LINGKUNGAN: STUDI KASUS DI PAPUA SELATAN - Diliana, Ekfindar; Ginting, Syahfitriani Br; Nggaruaka, Tobias (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to (1) explore the structure of nature-based curricula in South Papua, (2) explore the implementation of nature-based curricula in South Papua, and (3) determine the role of nature schools in promoting environmental sustainability in South Papua. The research method used is a qualitative approach with a case study conducted at nature schools in South Papua. Three schools implementing nature-based curricula were selected as samples. Data were collected through observation, questionnaires, and interviews, and analyzed qualitatively. The findings indicate that (1) the curriculum is an integrated combination of the K-13 Curriculum and the Gotong Royong Curriculum, emphasizing thematic, collaborative, and experiential learning approaches; (2) the implementation of the curriculum is reflected in various school activities such as classifying and recycling waste, cultivating natural resources—such as fish, sago, and rice—and processing and marketing them. Moreover, environmental preservation is implemented through local wisdom, which characterizes the unique curriculum of nature schools in South Papua; and (3) nature schools function as centers for environmental conservation and for raising students’ environmental awareness in South Papua. Students’ awareness of the need to protect sources of raw materials and to limit the harmful impact of human waste are two key areas emphasized in the nature-based school curriculum.